Good Management of Sub-district Local Funds : A Comparison between Rayong’s Subdistrict Local Funds with and without Organization Development, Rayong Province - Laohatchakulpong, Wimolporn (Journal of Health Science of Thailand, 2017)
This study was aimed at evaluating Rayong’s sub-district local fund management in three different aspects, namely fund management, participation level, and innovation level. In addition, a comparison was made between the sub-districts with and without organization development (OD). This quasi-experimental research included 63 local funds. In a simple random allocation, 31 local funds were in an experimental groups and 32 in comparing groups. Measurements were done before and after the organization development. Data were collected using a general questionnaire, a local fund evaluation form of the National Health Security Office, and in an interview of the local fund committee members. Descriptive statistics such as histogram, percentage, mean, and standard deviation were employed. Parametric methods, specifically unpaired and paired t-test, were also used. The study showed that the majority of Rayong local funds were old (73%), mid-sized (57.1%), reported to subdistrict administration organization (60.3%), and located in Klaeng District (25.4%). The responsible officers were mostly personnel of the subdistrict administration organization (57.1%). Based on the evaluation guidelines of the National Health Security Office, It was revealed that the case groups showed better management than the comparing groups (p < 0.05). Unpaired t-test between the two groups before the test phase showed no significant difference. The opposite was shown when compared between the two groups after the test phase. In summary, organization development training (OD) increases the efficiency level of the personnel of the local fund groups at a statistically significant level.